Compound heterozygous PLEC mutations in a patient of consanguineous parentage with epidermolysis bullosa simplex with muscular dystrophy and diffuse alopecia. (10th September 2014) - Yin, Jinghua; Ren, Yali; Lin, Zhimiao; Wang, Huijun; Zhou, Yun; Yang, Yong
Abstract Epidermolysis bullosa simplex with muscular dystrophy (EBS‐MD; OMIM 226670) is an autosomal recessive form of EBS, characterized by skin blistering at birth and delayed onset of muscle dystrophy. Mutations in PLEC, the gene encoding plectin, have been identified to be causal for EBS‐MD. We report a case of EBS‐MD with diffuse alopecia. Genetic study revealed the patient carrying compound heterozygous mutations in PLEC despite the consanguineous parentage.